Vascular Reactivity to Hypercapnia Is Impaired in the Cerebral and Retinal Vasculature in the Acute Phase After Experimental Subarachnoid Hemorrhage - Warner, Laura; Bach-Hagemann, Annika; Albanna, Walid; Clusmann, Hans; Schubert, Gerrit A.; Lindauer, Ute; Conzen-Dilger, Catharina (Frontiers in Neurology, 2022)
Objective: Impaired cerebral blood flow (CBF) regulation, such as reduced reactivity to hypercapnia, contributes to the pathophysiology after aneurysmal subarachnoid hemorrhage (SAH), but temporal dynamics in the acute phase are unknown. Featuring comparable molecular regulation mechanisms, the retinal vessels participate in chronic and subacute stroke- and SAH-associated vessel alterations in patients and can be studied non-invasively. This study is aimed to characterize the temporal course of the cerebral and retinal vascular reactivity to hypercapnia in the acute phase after experimental SAH and compare the potential degree of impairment. Methods: Subarachnoid hemorrhage was induced by injecting 0.5 ml of heparinized autologous blood into the cisterna magna of male Wistar rats using two anesthesia protocols [isoflurane/fentanyl n = 25 (Sham + SAH): Iso—Group, ketamine/xylazine n = 32 (Sham + SAH): K/X—Group]. CBF (laser speckle contrast analysis) and physiological parameters were measured continuously for 6 h. At six predefined time points, hypercapnia was induced by hypoventilation controlled via blood gas analysis, and retinal vessel diameter (RVD) was determined non-invasively. Results: Cerebral reactivity and retinal reactivity in Sham groups were stable with only a slight attenuation after 2 h in RVD of the K/X—Group. In the SAH Iso—Group, cerebral and retinal CO2 reactivity compared to baseline was immediately impaired starting at 30 min after SAH (CBF p = 0.0090, RVD p = 0.0135) and lasting up to 4 h (p = 0.0136, resp. p = 0.0263). Similarly, in the K/X—Group, cerebral CO2 reactivity was disturbed early after SAH (30 min, p = 0.003) albeit showing a recovery to baseline after 2 h while retinal CO2 reactivity was impaired over the whole observation period (360 min, p = 0.0001) in the K/X—Group. After normalization to baseline, both vascular beds showed a parallel behavior regarding the temporal course and extent of impairment. Conclusion: This study provides a detailed temporal analysis of impaired cerebral vascular CO2 reactivity starting immediately after SAH and lasting up to 6 h. Importantly, the retinal vessels participate in these acute changes underscoring the promising role of the retina as a potential non-invasive screening tool after SAH. Further studies will be required to determine the correlation with functional outcomes.